Studies of athlete biological passport biomarkers and clinical parameters in male and female users of anabolic androgenic steroids and other doping agents. Issue 4 (29th January 2020) - Börjesson, Annica; Lehtihet, Mikael; Andersson, Alexander; Dahl, Marja‐Liisa; Vicente, Veronica; Ericsson, Magnus; Ekström, Lena
Abstract: The use of anabolic androgenic steroids (AAS) and other performance enhancing substances can change over time, so there is a need to constantly update what substances are used and can be detected. Six women and 30 men anabolic androgenic steroid users were recruited who filled out an anonymous questionnaire about their use of performance enhancing substances during the past year. Sampling took place on a single occasion and included blood and urine collection. Our aim was to identify which doping agents can be detected in men and women self‐reporting AAS use. The first choice of substances differed between men (testosterone) and women (oxandrolone). The use of growth hormones was reported among men (10%) and women (50%). Growth hormone releasing factors/secretagogs were reported by about ~ 20% in both genders. Nandrolone was the most frequently detected anabolic androgenic steroid even in those who did not report use in the past year. Of the current male testosterone users, 82% exhibited testosterone/epitestosterone (T/E) ratios of > 4. Men with current testosterone use displayed 4‐fold and 6‐fold higher median T/E, respectively, when compared with recent and previous testosterone users ( P = 0.0001). Dermal testosterone use in women (n = 2) was not associated with a T/E ratio of > 4, but with supra‐physiological total serum testosterone concentrations. Changes in gonadotropins and hematological parameters were associated with the time of the last anabolic androgenic steroid intake in men, whereas in women these biomarkers were within the normal range. This highlights gender specific differences and indicates the need for additional biomarkers in female athletes. Abstract : This study highlights a gender specific problem and the need for additional biomarkers in female athletes. Here it is indicated that dermal testosterone use in women is not detectable with the traditional T/E biomarker despite supra‐physiological total testosterone serum concentrations.